Bortezomib and ixazomib protect firefly luciferase from degradation and can flaw respective reporter gene assays - Becker, Jonas Philipp; Clemens, Jannick; Theile, Dirk; Weiß, Johanna (Analytical biochemistry, 2016)
Firefly luciferase-based reporter gene assays are the most commonly used assays to investigate the transcriptional regulation of gene expression. However, direct interaction of tested compounds with the firefly luciferase leading to altered enzymatic activity may lead to misinterpretation of experimental data. When investigating the proteasome inhibitors bortezomib, carfilzomib, and ixazomib, we observed increased luminescence for bortezomib and ixazomib, but not for carfilzomib, in a pregnane-X-receptor (PXR) reporter gene assay, which was inconsistent with the mRNA expression levels of the main PXR target gene CYP3A4. To further scrutinize this phenomenon, we performed experiments with constitutively expressed firefly luciferase and demonstrated that the increase in cellular firefly luciferase activity is independent from PXR activation or CYP3A4 promoter. Using cell-free assays with recombinant firefly luciferase enzyme, we made the counterintuitive observation that firefly luciferase activity is inhibited by bortezomib and ixazomib in a reversible and competitive manner. This inhibition stabilizes the firefly luciferase enzyme against proteolytic degradation (e.g., toward trypsin), thereby increasing its half-life with subsequent enhancement of total cellular luminescence that eventually mimicked PXR-driven luciferase induction. These data show that particular compounds can strikingly interfere with firefly luciferase and once more illustrate the importance of careful interpretation of data obtained from luciferase-based assays.